Oxytocin: Old Hormone, New Drug - Jolanta Gutkowska; Marek Jankowski (MDPI AG, 2009)
Oxytocin (OT), traditionally associated with reproductive functions, was revisited recently, and several new functions in cardiovascular regulation were discovered. These functions include stimulation of the cardioprotective mediators nitric oxide (NO) and atrial natriuretic peptide. OT's cardiovascular outcomes comprise: (i) natriuresis, (ii) blood pressure reduction, (iii) negative inotropic and chronotropic effects, (iv) parasympathetic neuromodulation, (v) NO pathway involvement in vasodilatation and endothelial cell growth, (vi) anti-inflammatory and (vii) antioxidant activities as well as (viii) metabolic effects. In addition, we have reported abundant OT in the early developing heart with its capacity to generate cardiomyocytes (CMs) from mouse embryonic stem cells and stem cells residing in the heart. OT increases glucose uptake by cultured CMs, in normal, hypoxic and even in insulin resistance conditions. In experimentally-induced myocardial infarction in rats, continuous in vivo OT delivery improves the cardiac healing process and cardiac work, diminishes inflammation, and stimulates angiogenesis. Therefore, in pathological situations, OT plays an anti-inflammatory and cardioprotective role, enhancing vascular and metabolic functions, with potential therapeutic application(s).